If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2(x) + 4(y) = 184 Solving 2x + 4y = 184 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 2x + 4y + -4y = 184 + -4y Combine like terms: 4y + -4y = 0 2x + 0 = 184 + -4y 2x = 184 + -4y Divide each side by '2'. x = 92 + -2y Simplifying x = 92 + -2y

| -0.8+y=-0.66666667 | | 2x+4y=184 | | -0.16666667x=-0.9 | | 2mn-2mt=2sn-2st | | 12x-17=-89 | | r^2+3r-40= | | -2.7x+1.8=-2 | | 10y^2+17y+3= | | 9x^3-7x^2+11x^2-3x^3= | | .5x+.2(9-x)=3.30 | | ax+b=3b-a | | -30+x=x+23 | | 20r^2+16r+25r+20= | | p-7=4 | | 800-6*50=100-10*50 | | 45s^2+150s+125= | | -7x+3+5x=15 | | x^2-4xy+16y= | | 39.99+0.45m=49.99+0.40m | | x-15+8x-3=90 | | Z+z+6=2z-4 | | 3x+1=24 | | -16a^2+36= | | 3x+1=23 | | x-0.66666667=0.8 | | 13x^2+9x-4-7x^2+15x-6= | | 3x^2+45x+150=0 | | 36+-16a^2= | | 0.35x-15=0.25x | | 2(1+2n)=12+6n | | -12a^2+27= | | 9p-2n+4p+2n= | | 18a^2b^4-12ab^3-7a^2b^4+15ab^3= | | -0.83333333x=-0.9 | | 4x^2+72x+320=0 | | 35(2x-1)=7(x-4)+3x | | 4b+4=4(1+2b)-8 | | 9x+2x+6-x=10 | | 2x+2=129 | | 6x^2+36x-42=0 | | 72=-8(4a-5) | | .08=7.50+5x | | X^2-19+90=0 | | 3(5c+4d)+6(d-2c)= | | 0.6t-4=2 | | -6n-(n-1)=-6n+6 | | -128a^2+98= | | 1.3(8-b)+3.7b=5.2 | | t^3+7t^2-4t-28=0 | | .50x+13=9 | | 8r-18=-74+r | | 6x-3+3x=24 | | 12x-3y=6 | | 0.3x=3 | | s^3-q^3= | | h=vt-5t^2 | | 6-4(r+2)=-37+r | | 2(a-4)=6 | | 7(3-x)=21 | | 7x-4y=-12 | | -14+x=x+15 | | 2(x-1)-3(x+2)=3x+4 | | 4b+5=3b-9 | | c(x+2)-5=c(dx-2) | | x(x+2)+x=6 |